Underlying Factors of Entrepreneurial Intentions among Asian Students - Indarti, Nurul; Rostiani, Rokhima; Nastiti, Tur (UI Scholars Hub, 2010)
A survey among 650 undergraduate students in Asian countries, including Indonesia, Japan, South Korea, Taiwan, and Thailand, showed that student's entrepreneurial intentions and the determining factors varied from country to country. Generally, self-efficacy, environmental factors, age, and gender were found to have significant impact on entrepreneurial intentions among Asian students. However, the model could only explain 25.5% total variance of entrepreneurial intentions. it is expected that results of this research can give insights for government and universities to formulate policies and programs to cultivate entrepreneurial spirit among students.